Concurrent Neoadjuvant Chemoradiotherapy for Siewert II and III Adenocarcinoma at Gastroesophageal Junction. (June 2015) - Zhao, Qun; Li, Yong; Wang, Jun; Zhang, Jun; Qiao, Xueying; Tan, Bibo; Tian, Yuan; Shi, Gaofeng; Xu, Qian; Li, Ruxun; Liu, Yueping; Yang, Peigang
Abstract: Objective: This study was conducted to investigate the efficacy and safety of using a concurrent neoadjuvant chemoradiotherapy (a XELOX regimen) to treat adenocarcinoma of the gastroesophageal junction. Methods: Seventy-six patients having resectable adenocarcinoma at the gastroesophageal junction (T3/4, N+, M0) were recruited to participate and randomly assigned to either a chemoradiotherapy group or a surgery group. Patients in the chemoradiotherapy group were orally given capecitabine (1, 000 mg/m 2, twice daily for 14 days, days 1–14) and intravenous oxaliplatin (130 mg/m 2 on day 1) for 2 cycles. Radiotherapy was performed with a total of 45 Gy administered in 25 sessions for 5 weeks. Patients in the surgery group received only surgical intervention. Results: In the concurrent chemoradiotherapy group, the overall response rate was 55.6% (20/36), tumor control rate was 100% and a pathological complete response was achieved in 16.7% (6/36). The entire chemoradiotherapy group had R0 resections as did 80% of the surgery group (32/40) ( P < 0.05). In the concurrent chemoradiotherapy group, 6 patients developed grade 3 side effects. Treatment was either discontinued or the dose adjusted. Major hematological side effects in the chemoradiotherapy group included leukopenia, neutropenia, anemia and thrombocytopenia. Nonhematological side effects included nausea, vomiting and appetite loss. Chemoradiotherapy-related death was not observed. Conclusions: Concurrent neoadjuvant chemoradiotherapy administration increased the rate of R0 resection and demonstrated favorable safety in patients with Siewert II or III adenocarcinoma at the gastroesophageal junction. These results support the use of neoadjunctive chemoradiotherapy in the treatment of adenocarcinoma of the gastroesophageal junction.